Determinants and Performance of Regional Development Planning: Evidence from Nduga Regency, Papua, Indonesia - Hariman Usman; Elsyan R. Marlissa; Transna Putra Urip S (Goodwood Publishing, 2026)
Purpose: This study examines the factors influencing the performance of regional development planning in Nduga Regency and analyses the contribution of planning document consistency, integration, and quality. Research Methodology: A quantitative approach was employed using primary data collected through structured questionnaires administered to 56 respondents from 28 regional government organizations (OPDs) in Nduga Regency, via purposive sampling. Data were analyzed using structural equation Modelling based on Partial Least Squares (SEM-PLS) with WarpPLS 8.0 software, testing causal relationships among internal factors, external factors, and planning performance. Results: Internal factors, including document quality, process effectiveness, resource commitment, and implementation readiness, exerted a positive and significant effect on planning performance (P<0.01; R²=0.608; f²=0.608, large effect). External factors were positive but not statistically significant (P=0.08; R²=0.179; f²=0.179, medium effect). Conclusions: Internal organizational capacity and document alignment are the decisive determinants of regional development planning performance in the Nduga Regency. Despite extreme geographical isolation, endemic security disruption, and heavy fiscal dependency on the central government, the fundamental planning deficit is internal, with limited human resource competence, weak planning–budget linkage, and poor inter-agency coordination. Limitations: This study is limited by its focus on only 56 respondents from 28 regional government organizations (OPDs) in Nduga Regency, which may not fully represent the diverse perspectives across all regional departments. Contributions: This study provides valuable insights into the role of internal organizational capacity and document alignment in shaping regional development planning performance in the Nduga Regency.